Efficient and rapid adsorption characteristics of templating modified guar gum and silica nanocomposite toward removal of toxic reactive blue and Congo red dyes. (September 2015) - Pal, Sagar; Patra, Abhay Shankar; Ghorai, Soumitra; Sarkar, Amit Kumar; Mahato, Vivekananda; Sarkar, Supriyo; Singh, R.P.
Graphical abstract: Highlights: Modified guar gum and silica based nanocomposite was prepared via sol–gel method. g-GG acts as excellent template for uniform growth of silica nanoparticles. Nanocomposite demonstrated outstanding potential for removal of anionic dyes. Abstract: The present study highlights the potentiality of sol–gel synthesized guar gum-graft- poly (acrylamide)/silica (g-GG/SiO2 ) hybrid nanocomposite toward the rapid removal of toxic reactive blue 4 (RB) and Congo red (CR) dyes from aqueous solution. Various physicochemical characterizations support the feasibility of the functionalized guar gum matrix as efficient template for the formation of homogeneous nanoscale silica particles. The composite demonstrates rapid and superior adsorption efficiency of RB ( Qmax : 579.01 mg g −1 within 40 min) and CR ( Qmax : 233.24 mg g −1 within 30 min) dyes from aqueous environment. Here, the pH driven adsorption process depends strongly on the ionic strength of the salt solution. The adsorption kinetics data predicts that pseudo second-order (surface adsorption) and intraparticle diffusion take place simultaneously. The adsorption equilibrium is in good agreement with the Langmuir isotherm, while the thermodynamics study confirms spontaneous nature of the adsorption process. Desorption study predicts the excellent regenerative efficacy of nanocomposite.